2018
DOI: 10.1038/s41598-017-19096-x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral iron levels in children with attention-deficit hyperactivity disorder: a systematic review and meta-analysis

Abstract: There is growing recognition that the risk of attention-deficit hyperactivity disorder (ADHD) in children may be influenced by micronutrient deficiencies, including iron. We conducted this meta-analysis to examine the association between ADHD and iron levels/iron deficiency (ID). We searched for the databases of the PubMed, ScienceDirect, Cochrane CENTRAL, and ClinicalTrials.gov up to August 9th, 2017. Primary outcomes were differences in peripheral iron levels in children with ADHD versus healthy controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 61 publications
2
56
1
1
Order By: Relevance
“…There is a large body of evidence about iron deficiency during pregnancy and maternal and fetal outcomes [32]. Two recent systematic reviews and meta-analyses suggest that ADHD is related to lower serum ferritin levels in children [33,34]. Nonetheless, few studies have been published so far analyzing the association between maternal ferritin levels during pregnancy and long-term effects on child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence about iron deficiency during pregnancy and maternal and fetal outcomes [32]. Two recent systematic reviews and meta-analyses suggest that ADHD is related to lower serum ferritin levels in children [33,34]. Nonetheless, few studies have been published so far analyzing the association between maternal ferritin levels during pregnancy and long-term effects on child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia has irreversible adverse effects on childhood growth and development, even their working abilities in adulthood 7. Many studies suggested an association between anaemia and impaired psychomotor development; impaired cognitive functions such as concentration, intellectual status, memory and scholastic skills; psychological and behavioural disorders such as attention-deficit/hyperactivity disorder8 and autism spectrum disorder9 and decreased physical activity 10. Meanwhile, anaemia has been confirmed to be associated with impaired renal function, increased absorption of lead and impaired immunity 11.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the studies indicate lower serum ferritin levels in ADHD patients [ 32 , 33 , 69 , 70 , 71 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Other reports found no significant relationship [ 89 , 95 , 96 , 97 , 98 , 99 , 100 ]. Only one (older) publication claimed to find higher levels [ 28 ].…”
Section: Iron (Fe)mentioning
confidence: 87%